2018
DOI: 10.1021/acsnano.7b07223
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Matching at Metal/Molecule Contacts for Efficient Heterogeneous Charge Transfer

Abstract: In a metal/molecule hybrid system, unavoidable electrical mismatch exists between metal continuum states and frontier molecular orbitals. This causes energy loss in the electron conduction across the metal/molecule interface. For efficient use of energy in a metal/molecule hybrid system, it is necessary to control interfacial electronic structures. Here we demonstrate that electrical matching between a gold substrate and π-conjugated molecular wires can be obtained by using monatomic foreign metal interlayers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…[1] A monoatomic layer of foreign atoms can efficiently tune the interfacial metal/molecule electronic structure and thus the charge transfer kinetics. [2] More complicated supported or multi-component catalysts utilize the interfacial effects to enhance the catalytic reactions. [3] An in-depth understanding of the detailed atomic structure-molecule interaction is crucial to reveal the atomic and molecular level origin of the active sites in catalysis and interfacial electrochemical processes.T his becomes particularly important for the emerging frontier of single atom or few atoms catalysis where the role of specific atomic sites are dominating.…”
mentioning
confidence: 99%
“…[1] A monoatomic layer of foreign atoms can efficiently tune the interfacial metal/molecule electronic structure and thus the charge transfer kinetics. [2] More complicated supported or multi-component catalysts utilize the interfacial effects to enhance the catalytic reactions. [3] An in-depth understanding of the detailed atomic structure-molecule interaction is crucial to reveal the atomic and molecular level origin of the active sites in catalysis and interfacial electrochemical processes.T his becomes particularly important for the emerging frontier of single atom or few atoms catalysis where the role of specific atomic sites are dominating.…”
mentioning
confidence: 99%
“…39 The RDE has recently been used by Sato et al to study electron transfer to oxygen via catalysts tethered to gold electrodes. 40 The use of PEMUs on RDEs offers some additional potential benefits: first, the layer-by-layer addition of polymers, performed under ambient conditions, is rather "forgiving" of defects such as dust particles: each layer deposits over such defects. Second, the PEMU itself is amorphous and does not affect tunneling currents via phonons and crystal boundaries the way an inorganic layer such as BN or MgO might.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In their analysis of electron transfer kinetics, Feldberg and Sutin emphasized the advantages of a steady-state current at microelectrodes, a geometry recently used by Velický et al to explore tunneling through boron nitride (BN) films . The RDE has recently been used by Sato et al to study electron transfer to oxygen via catalysts tethered to gold electrodes …”
Section: Resultsmentioning
confidence: 99%
“…For instance, metal surfaces may contain terrace, step edge, kink, adatom, and corner sites with varying coordination environments and thus different chemical interactions with molecules . A monoatomic layer of foreign atoms can efficiently tune the interfacial metal/molecule electronic structure and thus the charge transfer kinetics . More complicated supported or multi‐component catalysts utilize the interfacial effects to enhance the catalytic reactions .…”
Section: Figurementioning
confidence: 99%
“…On the other hand, for the strong antibonding π* states, it interacts with d‐band through the back‐donation of electrons from metal d‐band to π* orbital, which weakens the NC bond and leads to the red‐shift of ν NC of CPI adsorbed on Pt compared to unbound molecule . It has been demonstrated that σ–d interaction is dominant for atop adsorption configuration while d–π* interaction governs for the adsorption with bridge and hollow configuration ,…”
Section: Figurementioning
confidence: 99%